Perbandingan Kecepatan Perahu 1 GT Menggunakan Propeller Dua Daun dan Tiga Daun Pada System Water Jet - Ikhsan, Muhammad; B, Siswandi; Jupri; Efrizal; Muhammad Ryan Saputra; Bima Kurniawan (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Indonesia, as an archipelagic country with extensive marine areas, relies on small vessels as the main means of transportation for coastal communities; therefore, an efficient, safe, and suitable propulsion system for shallow waters is required. This study aims to analyze the effect of the number of propeller blades on the speed of a 1 GT boat equipped with a water jet propulsion system. An experimental method was applied by conducting speed tests in shallow waters using a 4-inch diameter water jet and a 7 HP Rubin engine. The tests were carried out using two-blade and three-blade propellers, each tested four times on the same boat, engine, and location. Primary data were obtained from direct testing and speed measurements, while secondary data included engine specifications, 1 GT boat characteristics, and water jet design data. The analysis was conducted using descriptive and comparative methods. The results show that the three-blade propeller produced a higher average speed of 4.88 knots compared to 4.13 knots for the two-blade propeller. The maximum speed achieved by the three-blade propeller was 5.3 knots, while the two-blade propeller reached 4.4 knots. These results indicate that the three-blade propeller generates greater thrust, making it more effective for improving the speed of small boats using water jet systems in shallow waters.